Lycopene alleviates 5-fluorouracil-induced nephrotoxicity by modulating PPAR-γ, Nrf2/HO-1, and NF-κB/TNF-α/IL-6 signals - Ghadeer M. Albadrani; Ahmed E. Altyar; Osama A. Kensara; Mohie A.M Haridy; Amany A. Sayed; Zuhair M. Mohammedsaleh; Muath Q. Al-Ghadi; Rasha Mohammed Saleem; Mohamed M. Abdel-Daim (Renal Failure)
5-Fluorouracil (5-FU) is one of the most used anticancer drugs. However, its nephrotoxicity-associated drawback is of clinical concern. Lycopene (LYC) is a red carotenoid with remarkable anti-inflammatory and anti-oxidative properties. In this study, rats were divided randomly into five groups: control, lycopene (10 mg) (10 mg/kg/day; P.O), 5-FU (30 mg/kg/day; i.p.), Lycopene (5 mg) + 5-FU (5 mg/kg + 30 mg/kg/day), and lycopene (10 mg) + 5-FU (10 mg/kg + 30 mg/kg/day). LYC attenuated the loss of renal function induced by 5-FU in a dose-dependent manner. Rats co-treated with LYC had lower serum urea, creatinine, uric acid and KIM-1 levels, and a higher serum albumin level than those receiving 5-FU alone. Furthermore, co-treatment with the high dose of LYC maintained renal oxidant–antioxidant balance by ameliorating/preventing the loss of antioxidants and the elevation of malondialdehyde. Rats treated with 5-FU had markedly lower renal levels of PPAR-gamma, HO-1, Nfr2, and Il-10 and higher levels of NF-kB, TNF-alpha, and IL6 compared to the control rats. Co-treatment with LYC attenuated the reduction in PPAR-gamma, HO-1, Nfr2, and IL-10 levels and moderated the elevated levels of NF-kB, TNF-alpha, and IL-6. The kidneys from rats co-treated with lycopene (10 mg) + 5-FU did not show the degenerative changes in the glomerular tufts and tubules observed for the rats treated with 5-FU alone. In conclusion, LYC is a promising therapeutic strategy for attenuating 5-FU-induced nephrotoxicity through the restoration of antioxidant activities and inhibition of inflammatory responses by modulating PPAR-γ, Nrf2/HO-1, and NF-κB/TNF-α/IL-6, signals.